The river murders [compact disc, unabridged] - Patterson, James, 1947-; Born, James O (Patterson, James, 1947- Mitchum series., 2020)
Sometimes figuring out the truth means going to the point of no return. For Mitchum, returning isn't something he concerns himself with. In three "Bookshot" thrillers, the Navy SEAL reject-turned-private-eye has to solve some very high-stakes cases.